Clinical and Patient Reported Outcomes Following Peroneus Brevis Reconstruction with Hamstring Tendon Autograft. Issue 1 (January 2022) - Chrea, Bopha; Eble, Stephanie K.; Day, Jonathan; Hansen, Oliver B.; O'Malley, Martin J.; Ellis, Scott J.; Drakos, Mark C.
Category: Ankle; Other Introduction/Purpose: Peroneal tendon injuries are a common cause of lateral ankle pain and instability. While the use of hamstring autograft has been proposed as a viable surgical option for peroneus brevis reconstruction, reported outcomes with this technique are limited in the literature. We present patient-reported and clinical outcomes for patients who underwent peroneus brevis reconstruction with hamstring autograft. Methods: Thirty-one patients were retrospectively identified who underwent peroneus brevis reconstruction with hamstring autograft for peroneal tendinopathy between February 2016 and May 2019. All patients who had a peroneus brevis reconstruction were included and all concomitant procedures were noted. Patient-Reported Outcomes Measurement Information System (PROMIS) surveys were prospectively collected preoperatively and at a minimum of 1 year postoperatively (average 24.25, range 12-52.70) months. Retrospective chart review was performed to evaluate the incidence of postoperative complications and reoperations at an average of 30.23 (range, 14.62-53.72) months. Results: When evaluating pre and postoperative patient-reported outcome surveys (n=26; 84%), on average patients reported improvement in every PROMIS domain evaluated, with significant improvement in Physical Function (+5.99; p=0.006), Pain Interference (-8.11; p<0.001), Pain Intensity (-9.02; p<0.001), and Global Physical Health (+7.29; p=0.001). Three patients reported persistent pain at a minimum of 1 year postoperatively of which 2 required re-operation. No patient reported persistent pain or discomfort at the harvest site of the hamstring autograft. Conclusion: Patients undergoing peroneus brevis reconstruction with hamstring autograft experienced excellent patient- reported and clinical outcomes. Few postoperative complications were observed, and patients reported improvements across all patient-reported outcome domains, with significant improvements for pain and function domains. Reconstruction with hamstring autograft represents a viable surgical option in the setting of peroneal tendinitis or tears.